REGULASI INDUSTRI TELEKOMUNIKASI NASIONAL DALAM PERSPEKTIF HUKUM PERSAINGAN USAHA - Ari Purwadi (Perspektif, 2005)
Industrial regulation of telecommunication has been arranged by Act No. 36 Year 1999 that has given chances for pro-competition and anti-monopoly. Government policies on telecommunication have not opened the chances widely due to telecommunication performance exclusively or in such duopoly manner. Practically conducts that lead to unhealthy competitions in implementation of telecommunication are still found.